On the stability of Jeffcott rotor in fluid-film bearings - Stegić, Milenko; Vranković, Nikola; Kranjčević, Nenad (Computer Assisted Methods in Engineering and Science; Vol 9 No 4 (2002), 2023)
For some combinations of rotor speed and radial load, the pressure field of bearing fluid can perturb the pure rotational motion and disturb the normal operation of a rotating machine. Classical approach to the stability analysis of Jeffcott rotor in fluid-film bearings is modelling bearings as spring-damper elements and disregarding the external rotor damping [1, 5]. Nonlinear models are used to verify results obtained from a linearized model. This paper deals with the influence of external rotor damping on the size of stability regions. Stability analysis of the Jeffcott rotor in fluid-film bearings is performed by using both the linear model based on the linearization of bearing force around the static equilibrium position and the nonlinear model of the velocity linearization [2, 3].